147 Predictive factors associated with successful bilateral sentinel lymph node mapping in early-stage cervical cancer. (18th September 2019) - Bresset, A; Balaya, V; Magaud, L; Bonsang-Kitzis, H; Deloménie, M; Nguyen-Xuan, HT; Koual, M; Montero Macias, R; Ngo, C; Bats, AS; Mathevet, P; Lécuru, F
Abstract : Objectives: The objective of this study was to determine clinical, tumor and surgical factors associated with sucessful bilateral sentinel lymph node mapping (SBM) in early-stage cervical cancer. Methods: We performed an ancillary work on the data of two prospective trials on SLN biopsy for FIGO IA-IIA cervical cancer (SENTICOL I & II). Patients having a radical surgery with lymph node dissection were included between 2005 and 2012 from 25 French oncologic centers. Sentinel lymph node (SLN) was detected by a combined labeling technique (blue and isotopic). Results: 326 patients were included for analysis: SLNs were identified on at least one side of the pelvis in 308 patients (97.6%) and bilaterally in 278 patients (85.3%). No SLNs were found in 8 patients (2.4%). The mean age was 43 years [22–85 years]. Most patients (88.1%) had IB1 clinical FIGO stage. The majority of patients (71%) had squamous cells carcinoma. Surgeries were mainly performed by mini-invasive approach (296 patients – 90.8%) whereas 30 patients (9.2%) were operated by laparotomy. By multivariate analysis, SBM was associated with minimal invasive approach (ORa= 15.00, 95%CI = [1.24 – 181.63], p = 0.03) and inclusion during the period 2009–2012 (ORa= 14.81, 95%CI = [3.89 – 56.45], p < 0.0001) compared to the period 2005–2007. Age ≥ 70 years was significantly associated with lower SBM rate (ORa= 0.03, 95%CI= [0.004 – 0.20], p = 0.0002). Conclusions: A better experience of SLN biopsy technique, minimal invasive approach and patient age < 70 years were associated with better SBM rate in early-stage cervical cancer.